A new family of cinchona-derived bifunctional asymmetric phase-transfer catalysts: application to the enantio- and diastereoselective nitro-Mannich reaction of amidosulfones. - Johnson, K; Rattley, MS; Sladojevich, F; Barber, D; Nuñez, MG; Goldys, A; Dixon, D (2012)
A new family of bifunctional H-bond donor phase-transfer catalysts derived from cinchona alkaloids has been developed and evaluated in the enantio- and diastereoselective nitro-Mannich reaction of in situ generated N-Boc-protected imines of aliphatic, aromatic, and heteroaromatic aldehydes. Under optimal conditions, good reactivity and high diastereoselectivities (up to 24:1 dr) and enantioselectivities (up to 95% ee) were obtained using a 9-amino-9-deoxyepiquinidine-derived phase-transfer catalyst possessing a 3,5-bis(trifluoromethyl)phenylurea H-bond donor group at the 9-position.